Magnetic GO‐PANI decorated with Au NPs: A highly efficient and reusable catalyst for reduction of dyes and nitro aromatic compounds. (2nd June 2017) - Pourjavadi, Ali; Doroudian, Mohadeseh; Abedin‐Moghanaki, Azardokht; Bennett, Craig
Abstract : Due to the high activity of Au nanoparticles (NPs) for various reactions, many researchers have tried to develop heterogeneous catalysts in order to prevent irreversible agglomeration of Au NPs. Herein, magnetic graphene oxide modified with polyaniline (PANI) was used as a support for Au NPs that brings together advantages including: uniform dispersal of the catalyst in water, alarge surface area related to the graphene oxide; easy electron transfer in chemical reactions and good attachment of Au NPs to the support associated with PANI; and finally facile recovery in the presence of a magnetic field. Catalytic reduction of different analytes (Congo red, methylene blue, rhodamine B and 4‐nitro phenol) was evaluated in the presence of NaBH4 and the results show high catalytic activity of the catalyst. The catalyst was thoroughly characterized using various methods including FTIR, XRD, XPS, FE‐SEM and HRTEM analyses while its catalytic activity was evaluated via reduction of different analytes. Abstract : ‐synthesis of magnetic graphene oside modified with polyaniline as a heterogeneous support for Au nanoparticles. ‐comprehensive investigation of characteristics of the catalyst. ‐reduction of dyes and nitroaromatic compounds via a convenience method.